2002
DOI: 10.1159/000064153
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Enzymes Involved in Energy Production in the Small Intestine during Suckling-Weaning Transition of Pigs

Abstract: The effect of weaning on a potential metabolic capacity of key enzymes involved in the energy production by porcine enterocytes was investigated. The activity of citrate synthase, isocitrate dehydrogenase, α-ketoglutarate dehydrogenase, glutamate dehydrogenase, alanine aminotransferase and aspartate aminotransferase was determined in the small intestine epithelium of piglets during suckling-weaning transition. Investigations were performed on 5-week-old (suckling), 6-week-old (1st week after weaning) and 7-wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Because of limiting feed (energy) intake during the acute phase after weaning, glutamine contributes to alleviate intestinal alterations by providing gut tissue with fuel and precursors for defense systems ( Lallès et al, 2004 ). Madej et al (2002) also showed that the tricarboxylic acid cycle for transformation of a-ketoglutarate was from amino acids (e.g., glutamine, glutamate) than acetyl-CoA in the porcine small intestinal epithelium during suckling–weaning transition.…”
Section: Discussionmentioning
confidence: 96%
“…Because of limiting feed (energy) intake during the acute phase after weaning, glutamine contributes to alleviate intestinal alterations by providing gut tissue with fuel and precursors for defense systems ( Lallès et al, 2004 ). Madej et al (2002) also showed that the tricarboxylic acid cycle for transformation of a-ketoglutarate was from amino acids (e.g., glutamine, glutamate) than acetyl-CoA in the porcine small intestinal epithelium during suckling–weaning transition.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, epithelial cells in the pig intestine have notably high energy demands due to the rapid renewal of the epithelium (within few days) (2, 36). Previous studies showed the activities of key metabolic enzymes in enterocytes changed during the suckling-weaning transition in pigs (20,21). However, the effect of early weaning on the metabolism of enterocytes along the crypt-villus axis has not yet been elucidated.…”
mentioning
confidence: 99%
“…The results in the tables were presented as main effects. When no signi cant interaction between treatment and day was found, the differences among treatments or days were evaluated using Tukey HSD test (showed in Table 3,4,5,6). When signi cant interaction between treatment and day was found, a simple main effect analysis would be performed and the differences among 3 treatments across 2 levels of days post-weaning were evaluated using Bonferroni test (showed in Figure 1, 2, 3).…”
Section: Discussionmentioning
confidence: 99%
“…The intestine of piglet has notably high energy demand due to the repaid renewal of epithelium within few days [4,5]. Hence, the epithelial cells of gastrointestinal (GI) tract require intense anabolic metabolism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation